Gain-induced spectral non-degeneracy in type-II parametric down-conversion - Taheri, Behnood; Kopylov, Denis; Hammer, Manfred; Meier, Torsten; Förstner, Jens; Sharapova, Polina R. (arXiv)

Bipartite entanglement extracted from multimode squeezed light generated in lossy waveguides - Kopylov, Denis; Meier, Torsten; Sharapova, Polina R. (APL Quantum)
Entangled two-mode Gaussian states constitute an important building block for continuous variable quantum computing and communication protocols. In this work, we theoretically study two-mode bipartite states, which are extracted from multimode light generated via type-II parametric downconversion (PDC) in lossy waveguides. For these states, we demonstrate that the squeezing quantifies entanglement and we construct a measurement basis, which results in the maximal bipartite entanglement. We illustrate our findings by numerically solving the spatial master equation for PDC in a Markovian environment. The optimal measurement modes are compared with two widely used broadband bases: the Mercer–Wolf basis (the first-order coherence basis) and the Williamson–Euler basis.

Multiphoton, multimode state classification for nonlinear optical circuits - Kopylov, Denis; Offen, Christian; Ares, Laura; Wembe Moafo, Boris Edgar; Ober-Blöbaum, Sina; Meier, Torsten; Sharapova, Polina; Sperling, Jan
We introduce a new classification of multimode states with a fixed number of photons. This classification is based on the factorizability of homogeneous multivariate polynomials and is invariant under unitary transformations. The classes physically correspond to field excitations in terms of single and multiple photons, each of which being in an arbitrary irreducible superposition of quantized modes. We further show how the transitions between classes are rendered possible by photon addition, photon subtraction, and photon-projection nonlinearities. We explicitly put forward a design for a multilayer interferometer in which the states for different classes can be generated with state-of-the-art experimental techniques. Limitations of the proposed designs are analyzed using the introduced classification, providing a benchmark for the robustness of certain states and classes.